Nilai-Nilai Pendidikan KH. Ahmad Dahlan dalam Menghadapi Tantangan Pembelajaran PAI di Era Society 5.0: Studi Library Research - Kharisma Azam Rangkuti; Hazizah Isnaini; Yuspan Jailani Lubis; Okrigana Wirian (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study aims to analyze the relevance of KH Ahmad Dahlan's educational values in addressing the challenges of Islamic Religious Education (PAI) learning in the Society 5.0 era. Employing a library research approach, data were collected from primary and secondary sources, including scientific journals, books, and official documents related to Ahmad Dahlan's educational thought and the concept of Society 5.0. The collected data were analyzed using content analysis and comparative analysis to identify the alignment between Ahmad Dahlan's educational philosophy and contemporary educational demands. The findings reveal that Ahmad Dahlan's educational values, encompassing tajdid (renewal), ijtihad (independent thinking), the integration of religious and general sciences, noble character development, and social service, remain highly relevant to the challenges facing PAI learning in the Society 5.0 era, which is characterized by the convergence of digital technology, artificial intelligence, and the need for 21st-century competencies. These values provide a balanced educational framework that integrates technological advancement with moral and spiritual development. Therefore, this study recommends reconstructing the PAI curriculum based on Dahlanian educational values to create innovative, adaptive, and technology-responsive learning while maintaining the primary goal of developing insan kamil who possess strong religious, intellectual, and social competencies.